Encapsulation of aromatic coconut water with sodium alginate and calcium chloride - Thanapop Soteyome; Sumapa Thedkwanchai (Caspian Journal of Environmental Sciences)
The main goal of this study was to determine the best amount of sodium alginate needed to effectively encapsulate aromatic coconut water using sodium alginate and calcium chloride. Additionally, the study aimed to explore how physical and chemical factors influence the production of aromatic coconut encapsules. Finally, the research sought to evaluate consumer acceptance of encapsulated coconut aroma. The findings revealed that using 2 g sodium alginate per 200 g coconut water, 500 g clean water, and 3 g calcium chloride resulted in suitable viscosity of the encapsulated aromatic coconut. These encapsulations were able to dissolve into water when used in encapsulated or coated tablets. When incorporating varying amounts of sodium alginate (2, 2.5, and 3 g) into the aromatic coconut water, the colour and brightness value (L*) of the encapsulated product was found to be 45.18 ± 0.03, with a red value (a*) of -0.50 ± 0.01 and a yellow value (b*) of -3.12 ± 0.01. The pH value remained consistent at 5.20 ± 0.00, and the total dissolved solids (๐Brix) were 6.43 ± 0.00. No significant differences were observed in the sugar solid solution. Microbial analysis indicated that the quantity of microorganisms did not exceed the specified standard. In terms of consumer acceptance, 76% of the participants expressed satisfaction with the encapsulated coconut water.